2004
DOI: 10.1021/jm049768a
|View full text |Cite
|
Sign up to set email alerts
|

Substituted 3-Imidazo[1,2-a]pyridin-3-yl- 4-(1,2,3,4-tetrahydro-[1,4]diazepino- [6,7,1-hi]indol-7-yl)pyrrole-2,5-diones as Highly Selective and Potent Inhibitors of Glycogen Synthase Kinase-3

Abstract: Glycogen synthase kinase-3 (GSK3) is involved in signaling from the insulin receptor. Inhibitors of GSK3 are expected to effect lowering of plasma glucose similar to insulin, making GSK3 an attractive target for the treatment of type 2 diabetes. Herein we report the discovery of a series of potent and selective GSK3 inhibitors. Compounds 7-12 show oral activity in an in vivo model of type II diabetes, and 9 and 12 have desirable PK properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…Previous studies reported that the treatment of lithium, an inhibitor for both GSK3β enzymatic activity and inositol metabolism circuits, increased bone mass in animals with age-related osteoporosis and oophorectomy-induced osteoporosis394041. In this study, we found that wedelolactone directly inhibited the activity of GSK3β, suggesting that wedelolactone was an inhibitor of GSK3β (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies reported that the treatment of lithium, an inhibitor for both GSK3β enzymatic activity and inositol metabolism circuits, increased bone mass in animals with age-related osteoporosis and oophorectomy-induced osteoporosis394041. In this study, we found that wedelolactone directly inhibited the activity of GSK3β, suggesting that wedelolactone was an inhibitor of GSK3β (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…To induce osteoblast differentiation, normal culture medium (NM, as described above) was supplemented with freshly added ascorbic acid (50 µg/ml; Merck Inc., Kenilworth, NJ), β‐glycerophosphate (5 mM; Sigma–Aldrich), and dexamethasone (0.1   µM; Sigma–Aldrich) with or without recombinant human BMP‐2, BMP‐ 6 (50 ng/ml; R&D Systems, Minneapolis, MN) or a specific GSK3β inhibitor (GIN; 10nM; kindly provided by Dr. Rawadi, Prostrakan, France; Engler et al25) Cell cultures were subjected randomly to either BMP‐2 or BMP‐6. The culture medium was replaced every 3 to 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…34 Sequential Boc protection of the secondary amine, tosylation of the hydroxyl group and sodium hydride-assisted cyclization 34 gave the intermediary 1,2,3,4-tetrahydro-[1,4]diazepino[6,7,1- hi ]indoles 43a and 43b . Glyoxylation with ethyl chlorooxoacetate, condensation with benzofuran-3-yl-acetamide and subsequent Boc deprotection afforded the maleimides 24 and 25 .…”
Section: Chemistrymentioning
confidence: 99%